Designers' guide to eurocode 5 : design of timber buildings : En 1995-1-1 - Porteous, Jack (Designer's guide to the eurocodes., 2013)
This guide interprets and assists in the use of EN 1995-1-1 structural timber. Showing typical material properties and dimensions; modifiers, and structural responses, it presents concise worked examples.